THE INFLUENCE OF LEADERSHIP STYLE, WORK DISCIPLINE AND COMPETENCE ON EMPLOYEE PERFORMANCE AT THE DIRECTORATE GENERAL OF HUMAN RIGHTS - Efendi, Suryono; Sugiono, Edi; Dermanti, Estorina Lambok (2021)
This study aims to ascertain the relationship between leadership style, work discipline, competence, and employee performance at the Directorate General of Human Rights. This study employs a quantitative technique combined with a descriptive analysis. Primary and secondary data are offered in this study. The primary data sources are the responses to questionnaires distributed to correspondents. The preliminary data in this study comes from the correspondent's response to the questionnaire, while the secondary data comes from the Directorate General of Human Rights' profile and financial situation. The sample size for this study was reduced to a maximum of 150 persons. Validity, Reliability, Data Normality, and Hypothesis Testing are all terms that are used to describe how study data is analyzed. The research and discussion findings indicate that the leadership style has a positive and significant effect on employee performance at the Directorate General of Human Rights, work discipline has a positive but not statistically significant effect on employee performance at the Directorate General of Human Rights, and the competence has a positive and statistically significant effect on employee performance at the Directorate General of Human Rights.